Determinasi Kepatuhan Pajak: Integrasi Faktor Psikologi Sosial, Penegakan Hukum, dan Digitalisasi - Adhalia Tryani; Rina Tjandra Kirana DP (GLOBAL SCIENTS PUBLISHER, 2026)
Tax compliance is a multidimensional phenomenon that requires an integrated approach between social psychology, law enforcement, and digital transformation. This systematic literature review (SLR) aims to map the integration of these three pillars by synthesizing findings from 18 selected journals indexed in Scopus and Sinta. Following the PRISMA protocol, the study utilizes the Slippery Slope Framework (SSF) and Theory of Planned Behavior (TPB) to analyze how digitalization acts as a